Step‐down vs. step‐up noxious stimulation: differential effects on pain perception and patterns of brain activation. Issue 1 (10th September 2015) - Choi, J. C.; Kim, J.; Kang, E.; Choi, J.‐H.; Park, W. Y.; Choi, Y.‐S.; Cha, J.; Han, C.; Park, S. K.; Kim, M. H.; Lee, G. H.; Do, H.‐J.; et al.
Abstract : Background: We hypothesize that pain and brain responses are affected by changes in the presentation sequence of noxious stimuli that are, overall, identical in intensity and duration. Methods: During functional magnetic resonance imaging (fMRI) scanning, 21 participants experienced three patterns of noxious stimulation: Up‐type (step‐up noxious stimulation, 15 s), Down‐type (step‐down noxious stimulation, 15 s), and Down–up‐type (decreasing and increasing pattern of noxious stimulation, 15 s). The total intensity and duration of the three noxious stimulation patterns were identical, but the stimulation sequences were different. Results: Pain and unpleasantness ratings in the Down‐ and Down–up‐type noxious stimulations were lower than in the Up‐type noxious stimulation. The left prefrontal cortex [(PFC, BA (Brodmann area) 10, (−45, 50, 1)] was more highly activated in the Down‐ and Down–up‐type noxious stimulations than in the Up‐type noxious stimulation. The S1, S2, insula, bilateral PFC (BA 46), and midcingulate cortex were more highly activated in the Up‐type noxious stimulation than in the Down‐type noxious stimulation. PFC BA 10 was located at an inferior level compared to the bilateral PFC BA 46 ( Z axis = 1 for BA 10, compared to 22 and 25 for the right and left BA 46, respectively). When cortisol level was increased, the left hippocampal cortex, along with the left parahippocampal cortex, was greatly activated for the Up‐type noxious stimulation. Conclusion: When pain cannot be avoided in clinical practice, noxious stimuli should be applied to patients in a step‐down pattern that delivers the most intense pain first and the least intense pain last.